Werbeblocker im Internet Eine Beurteilung nach dem Urheber- und Lauterkeitsrecht, zugleich ein Beitrag zum Begriff des Mitbewerbers im Lauterkeitsrecht - Jung, Jonathan (Schriften zum geistigen Eigentum und zum Wettbewerbsrecht, 2021)
Ad blockers touch on numerous, as yet unresolved legal issues. While ad blockers have so far been judged primarily on the basis of unfair competition law, this work shows that the decisive factor is rather copyright law. This theme is developed with regard to the current case law jurisdiction of the ECJ. Furthermore, the concept of the ,competitor' in unfair competition law is developed and placed on a new foundation with reference to the transactional decision. The thesis also comprehensively analyzes the legality of the possible alternative actions of the website operators and the response options of the ad blockers from the perspective of unfair competition law, copyright law and takes into account the GDPR.